The Influence Of Work Democracy Leadership Style On Employee Performance At The West Binjai Sub-District Office - Bobby Arisandi; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of democratic leadership style on employee performance at the West Binjai Sub-district Office. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 80 people taken by prposive sampling. Based on the results of data analysis, this study found that democratic leadership style has a positive and significant influence on employee performance. The results of the hypothesis test showed a t-count value of 42.665, which is greater than the t-table 1.99085, with a significance value of 0.000 which is smaller than 0.05. The regression coefficient shows that each increase in the unit of democratic leadership style will lead to an increase in employee performance by 0.957 units, assuming other variables are considered fixed. In addition, the results of the determination test show that democratic leadership style can explain 95% variability in employee performance, which shows a very high influence. The remaining 5% is influenced by other factors that have not been researched. Thus, the democratic leadership style is proven to have a positive and significant influence on the performance of employees at the West Binjai Sub-district Office.